2017
DOI: 10.4310/jdg/1493172094
|View full text |Cite
|
Sign up to set email alerts
|

Localized mirror functor for Lagrangian immersions, and homological mirror symmetry for $\mathbb{P}^1_{a,b,c}$

Abstract: This paper gives a new way of constructing Landau-Ginzburg mirrors using deformation theory of Lagrangian immersions motivated by the works of Seidel, Strominger-Yau-Zaslow and Fukaya-Oh-Ohta-Ono. Moreover we construct a canonical functor from the Fukaya category to the mirror category of matrix factorizations. This functor derives homological mirror symmetry under some explicit assumptions. As an application, the construction is applied to spheres with three orbifold points to produce their quantum-corrected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(110 citation statements)
references
References 50 publications
0
110
0
Order By: Relevance
“…where φ(q) and ψ(q) are series in q, and − log q is the area of the minimal XY Z triangle (see [CHL,Section 6.1], where q α there is denoted by q here). By a change of coordinates on (x, y, z), W can be rewritten as…”
Section: Enumerative Meaning Of Mirror Maps Of Elliptic Curve Quotientsmentioning
confidence: 99%
“…where φ(q) and ψ(q) are series in q, and − log q is the area of the minimal XY Z triangle (see [CHL,Section 6.1], where q α there is denoted by q here). By a change of coordinates on (x, y, z), W can be rewritten as…”
Section: Enumerative Meaning Of Mirror Maps Of Elliptic Curve Quotientsmentioning
confidence: 99%
“…Cho, Hong, and Lau [4] described open Gromov-Witten potentials for elliptic orbifolds (and homological mirror symmetry). Explicit expressions for these were computed by Cho, Hong, Kim, and Lau [3].…”
Section: Intorduction and Statement Of Resultsmentioning
confidence: 99%
“…In this section, we recall the formalism of localized mirror functors developed in [6] and [7]. Later we will use this to understand Kapustin-Li pairing in terms of Lagrangian Floer theory.…”
Section: Localized Mirror Functorsmentioning
confidence: 99%
“…In fact, in the above work in progress, they discuss all cases P 1 a,b,c with bulk deformation by twisted sectors. In [6], it is shown that…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation